Orbital reconstruction: titanium mesh implant after excision of orbitozygomaticomaxillary tumors - Wolfs, Elias; Thatcher, Graham P.; Soukup, Jason W. (Frontiers in Veterinary Science, 2024)
Pathologic lesions of the orbitozygomaticomaxillary complex (OZMC) and caudal oral cavity can be a challenge in veterinary oromaxillofacial surgery. Neoplastic lesions that are in close proximity to or invading the orbit may result in significant loss of structural integrity after curative intent surgery. This in turn may alter the topography of the bulbous oculi (globe) with resultant enophthalmos, diplopia, and entropion. Historically, orbital exenterations have been deemed a suitable option to avoid these complications. However, lesions that do not include the globe in the surgical margin may be overtreated by irreversible orbital exenterations. Orbital reconstruction methods that ameliorate these consequences could be advantageous. A novel approach to reconstruct the orbit with a titanium mesh implant is described and the clinical and ophthalmic outcomes reported.